Transcriptomic analysis reveals the crucial role of YABBY genes family in hormonal induced parthenocarpy in Cucumis sativus L. - Tingting Liu; Rahat Sharif; Zetao Shi; Kehong Guo; Zhisen Zhang; Xueping Bao; Ahmad Ali (BMC Plant Biology)
Abstract Background The plant-specific YABBY transcription factor family plays several activities, including responding to abiotic stress, establishing dorsoventral polarity, and developing lateral organs. Cucumis sativus L. commonly referred to as cucumber and one of the first vegetable crops with a fully sequenced genome. Results In this work, we examined the application of NAA, CPPU, and GA4 + 7 to inflict parthenocarpy in the cucumber ZK line. The expression pattern of YABBY genes throughout fruit development and performed a genomic census of cucumber (Cucumis sativus L.). Based on peptide classification, we discovered eight CsYABBY genes and divided them into five subfamilies. Similarities in motif composition and exon-intron structure were also observed. The cis-elements and gene ontology (GO) analysis revealed the involvement of CsYABBY genes in vegetative growth and the transition of vegetative to the reproductive phase. The expression analysis revealed the differential expression response to NAA, CPPU, and GA4 + 7. In particular, the CsYABBY1 was induced sharply by NAA and CPPU but not GA4 + 7. The transient expression of CsCRC disclosed that it is localized in the nucleus. Conclusion These findings point to the possibility that CsYABBY1 and CsCRC may positively affect fruit development and could be utilized to generate parthenocarpic cucumber fruits.